2022
DOI: 10.1021/acsami.2c14031
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Gold-Coated Mesoporous Polydopamine Nanoprobe to Enhance Chemodynamic Therapy by Self-Supplying H2O2 and Photothermal Stimulation

Abstract: Tumor microenvironment (TME) responsive chemodynamic therapy (CDT) showed an important application in inhibiting tumor growth by producing the highly toxic hydroxyl radical (·OH), but insufficient hydrogen peroxide (H2O2) and overexpressed glutathione (GSH) limited its application. Herein, by integrating photothermal therapy (PTT) and CDT, a new kind of mesoporous polydopamine (MPDA)-based cascade-reaction nanoplatform (MPDA@AuNPs-Cu) was designed for enhanced antitumor therapy, in which ultrasmall gold nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…MPDA was synthesized through a modified method according to previous research. 42,43 Briefly, a seed solution was prepared via ultrasonically dissolving 0.9 g dopamine hydrochloride and 0.6 g F127 in the mixture of deionized water and ethanol (1 : 1). Then, 960 μL 1,3,5-trimethylbenzene (TMB) was introduced into above solution under sonication for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…MPDA was synthesized through a modified method according to previous research. 42,43 Briefly, a seed solution was prepared via ultrasonically dissolving 0.9 g dopamine hydrochloride and 0.6 g F127 in the mixture of deionized water and ethanol (1 : 1). Then, 960 μL 1,3,5-trimethylbenzene (TMB) was introduced into above solution under sonication for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The above results indicated that ultrasmall AuNPs possessed excellent self-supplying H 2 O 2 capability, which was stronger than natural GOx. 52…”
Section: Resultsmentioning
confidence: 99%
“…The above results indicated that ultrasmall AuNPs possessed excellent self-supplying H 2 O 2 capability, which was stronger than natural GOx. 52 By measuring the UV-vis absorption spectra of MB, the OH generation performance of ZIF-67@AuNPs@MnO 2 was evaluated. Firstly, by measuring the UV-vis absorption spectra of pure MB, the stability of MB was demonstrated (Fig.…”
Section: H 2 O 2 / Oh Generation Performancementioning
confidence: 99%
“…2 Currently, various combination therapies are available. According to different tumor microenvironments (TMEs), such as lower pH, 3 higher glutathione (GSH), [4][5][6] and excessive expression of folic acid receptors in cancer cells, 7,8 these characteristics have also been applied in combination therapy to achieve effects that cannot be achieved by a single treatment method. With the development of nanomedicine, multi-functional materials can be passively targeted into the tumor interior through the enhanced permeability and retention (EPR) effect so that targeted therapy can be performed at the tumor site.…”
Section: Introductionmentioning
confidence: 99%